2016
DOI: 10.1590/s0100-204x2016000900060
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade do feijoeiro cultivado sobre palhadas de gramíneas e adubado com nitrogênio em plantio direto

Abstract: Resumo -O objetivo deste trabalho foi avaliar a influência de doses de nitrogênio em cobertura e das palhadas de milho, de milho consorciado com braquiária e de braquiária sobre a produtividade e a qualidade de grãos do feijoeiro. O experimento foi realizado em área irrigada, no cultivo de inverno, após cinco anos da implantação do sistema plantio direto, em Latossolo Vermelho eutroférrico de textura argilosa. Utilizou-se o delineamento de blocos ao acaso com parcelas subdivididas e três repetições. As parcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
(20 reference statements)
1
15
0
2
Order By: Relevance
“…The biological N fixation does not supply an adequate amount of N to bean plants (Coelho et al, 1998;Silva et al, 2004). Furthermore, several researchers have reported that N fertilization improves nutritional and yield parameters of common bean (Silva et al, 2004;Amaral et al, 2016). However, there is still a great lack and conflict of information related to the amount of N provided on the physiological aspects of the common bean seeds.…”
Section: Introductionmentioning
confidence: 99%
“…The biological N fixation does not supply an adequate amount of N to bean plants (Coelho et al, 1998;Silva et al, 2004). Furthermore, several researchers have reported that N fertilization improves nutritional and yield parameters of common bean (Silva et al, 2004;Amaral et al, 2016). However, there is still a great lack and conflict of information related to the amount of N provided on the physiological aspects of the common bean seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment irrigated 2013, grain yield was increased by topdressing N fertilization up to the estimated rate of 124 kg ha -1 . Crusciol et al (2007), Kaneko et al (2010), Soratto et al (2014), Amaral et al (2016), and Soratto et al (2017) also reported increases in the grain yield of common bean due to soil-applied N fertilization, which was related to the expressive effect of this nutrient on plant growth and fruiting. The foliar application of 5.0 kg ha -1 N-SR resulted in the highest grain yield, with an increase of 395 kg ha -1 (15.7%) compared with the control and of 253 kg ha -1 (9.5%) with the treatment with 2.5 kg ha -1 N-CU.…”
Section: Resultsmentioning
confidence: 81%
“…Nitrogen is the nutrient taken up in the greatest amount by the common bean crop (Perez et al, 2013;Soratto et al, 2013); therefore, its supply at suitable rates and times is fundamental for obtaining a high grain yield (Soratto et al, 2011(Soratto et al, , 2014(Soratto et al, , 2017Amaral et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com Rossi et al (2012), a rápida liberação de P no período inicial da decomposição da braquiária está relacionada com a perda de P solúvel em água acumulada nos vacúolos dos resíduos vegetais, o que contribui para aumentar a disponibilidade do P para as plantas. Amaral et al (2016), estudando o efeito de diferentes palhadas sobre a produtividade do feijoeiro, também encontram maiores valores nas parcelas com palhada de braquiária (U. ruziziensis). Os dados de produtividade apresentaram comportamento quadrático em função das doses de P 2 O 5 , cuja dose de máxima eficiência agronômica foi calculada por meio da derivada primeira da equação e correspondeu a 234,58 kg ha -1 de P 2 O 5 (Figura 2).…”
Section: Avaliações No Feijoeirounclassified